"In addition to Abdziralovič": characteristic of the life and work of Ihnat Kančeŭski. - Novick, Ivan М. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the life and works of Ihnat Kančeŭski, better known under the pseudonym Ignat Abdziralovič - author of the famous essay “Advečnym šlacham” (“By the everlasting way”). Our main conclusion is as follows: the main, almost the only topic Kančeŭski as publicist was cooperation – this topic was riveted on his attention, to it he returned again and again, through the framework of cooperation he analyzed other cultural and social phenomena of the Belarusian life. A significant part of his biography and practical life was associated with cooperation. Therefore, its appearance in the pages of "Advečnym šlacham" is not a coincidence - just these few pages bear the brunt of political philosophy of Kančeŭski, here one should look for the key to understanding of his social outlook.
Keywords: Ignat Abdziralovič; Ignat Kančeŭski; history of Belarusian philosophy